Soil microplastic pollution shifts relative dominance in competition between native and invasive plants - Mingyan Li; Huizhen Zou; Zhihang Sun; Qiang Wang; Yanni Chen; Lina Xu; Change Zhou; Xianhu Guo; Shaoxia Guo; Chixuan Xiang; Xiaolei Jiang; Tong Wang; et al. (Applied Soil Ecology, 2026)

Allelochemical-mediated bacterial homogenization and its potential role in mitigating chemical stress induced by plant invasion in alpine meadows - Xin Liu; Yaojun Ye; J. Aaron Hogan; Wenguang Sun; Minshu Song; Hang Sun; Yazhou Zhang (Applied Soil Ecology, 2026)

Synergistic Effects of Biochar and Nitrogen Fertilizer on Soil Humification and Japonica Grain Yield in Black Soil Paddy Systems of Northeast China - Pingxin Liu; Haihang Sun; Jingwei Gao; Nan Wang; Shuai Wang (Journal of Soil Science and Plant Nutrition, 2026)

Cross-kingdom gut microbial networks are associated with farming-system-related variation in muscle quality of largemouth bass (Micropterus salmoides) - Kai Hu; Guangdi Hu; Huidie Hu; Hanchang Sun (Aquaculture, 2026)

Research on nonlinear seepage of full flow regimes in a rough single fracture using boundary layer theory and fractal geometry - Wenjie Yang; Yong Huang; Kehan Miao; Jie Zhang; Xiaochang Sun (Advances in Water Resources, 2026)

Aging or degradation? Transformation mechanisms of microplastics in soil environments - Xingyu Zhong; Liyuan Qiang; Jinping Cheng; Zhihang Sun; Huibing Hu; Han Liu; Ruoyu Zhang (Applied Soil Ecology, 2025)

Inorganic nanoparticles for use in aquaculture - Seerengaraj Vijayaram; Konstantina Tsigkou; Antonio Zuorro; Yun‐Zhang Sun; Holy Rabetafika; Hary Razafindralambo (Reviews in Aquaculture, 2023)
Nanotechnology is a rising technology dealing with nanoparticle‐based (1–100 nm) organic and inorganic materials. Such technology has a vital role in various industrial sectors, including pharmaceuticals, nuclear energy, fuel and energy, electronics, and bioengineering, while having potential applications to human, animal, plant, and environmental health. Even though nanomaterial applications can cover multi‐areas of biological and natural fields, limited information are available in the aquaculture sector. Nowadays, the aquaculture sector is the most imperative field to meet animal protein requirements for human nutrition, and aquaculture disease outbreaks as well as the aquatic environment pollutants are significant hindrances in producing healthy aquatic products. The current review aims to enlighten the direction of nanotechnology in the aquaculture industry while providing more specific information about inorganic forms of nanoparticles used to develop several types of applications such as antimicrobial, antibiofilm and photocatalytic agents, as well as aquatic animal nutrition in the domain of aquaculture. A large number of inorganic nanoparticles and their use as animal feed and for water treatment are extensively described. Their potential risks in aquaculture are also presented and discussed. The aquaculture nanotechnology applications are expected to contribute to fish health improvement, harmful microbes control, and aquatic products nano‐delivery in the forthcoming years.